General correlation between R3 test results and compressive strengths for five families of supplementary cementitious material - Koufany, Imane; Gómez-de-la-Torre, María de los Ángeles; Redondo-Soto, Cinthya; Santacruz-Cruz, María Isabel; Cuesta-García, Ana María; Gastaldi, Daniela; Canonico, Fulvio; Mazanec, Oliver; García-Aranda, Miguel Ángel (Elsevier, 2025)
The incorporation of locally available supplementary cementitious materials (SCMs) in cement blends is essential for reducing the environmental impact of construction. However, assessing the pozzolanic kinetics, and thus the pozzolanic contribution at a given age, is challenging due to temperature differences between the two main evaluation methods: ASTM C1897 (40 °C, continuous heat release) and ASTM C311 (20 °C, Strength Activity Index at 28 days). This study examines 22 SCMs, analysing their composition, mineralogy, texture, and pozzolanic behaviour. ASTM C1897 was applied as prescribed, while ASTM C311 was modified by maintaining a constant water-to-binder ratio and introducing an additional 68 % PC–20 % SCM–10 % limestone–2 % gypsum series to better isolate pozzolan effects. The results confirmed established pozzolanic trends, with kaolinite-rich calcined clays ≳ silica fume > smectite-rich calcined clays > natural pozzolans ≳ class-F fly ashes. The modified series yielded clearer correlations, particularly between SAI2°C28d and Heat4°C3d, forming two well-defined clusters that reflect general behaviour. These findings suggest that the modified series could serve as a more reliable framework for future SAI evaluations. Moreover, for the 80 % PC–20 % SCM, the best correlation is found for the R3-heat release at 12 h (at 40 °C) and the SAI values at 28 days (at 20 °C). Additional insights into the pozzolanic kinetics and performance of the materials are also presented, contributing to a deeper understanding of their potential in sustainable construction practices.
Funding for open access charge: Universidad de Málaga/CBUA.
CSA Research LLC (USA) is thanked for funding I.K. PID2020-114650RB-I00 grant from Ministry of Science and Innovation of Spain, co-funded by ERDF, is thanked for partial financial support. Escuela de Ingenierías Industriales of Universidad of Málaga is thanked for providing the devices funded by Junta de Andalucía and ERDF (IE19_182 UMA grant) to perform the mechanical strength tests. The authors thank Ms. B. Guirado-Rodríguez, Ms. E. M. Benjumea-Rejano, and Mr. F. Gómez-García for assisting with some of the SAI tests.
Keywords: Cemento Portland; Cemento - Industria; Minerales de arcilla; Pozzolanic reactivity; Pozzolanic reaction rate; Strength activity index; Blended cements; Smectitic calcined clays; Natural pozzolans; Kaolinitic calcined clay; Fly ash